GENDER DAN KOMUNIKASI POLITIK : IBU NYAI DALAM MEMOBILISASI SUARA PADA PILKADA BANGKALAN 2024 - Dina Mukarromah; Laila Kholid Alfirdaus (Journal of Politic and Government Studies, 2026)
angkalan is known as the “City of Santri,” characterized by a religious society that is obedient to religious scholars. In this context, Ibu Nyai emerges as a female religious leader with strong authority and charisma, not merely as the wife of a kiai. She plays a role in bridging women’s participation in the public sphere within a strongly patriarchal culture. The Bangkalan regional election (Pilkada) serves as a space for political participation as well as a contestation of cultural and religious influence. The involvement of Ibu Nyai in the campaign is an interesting subject of study to examine her role in practical politics through political 1Mahasiswa Ilmu Pemerintahan Universitas Diponegoro 2Dosen Ilmu Pemerintahan Universitas Diponegoro communication as a form of women’s representation. Cultural feminism is used as an analytical framework to understand her role, particularly in utilizing cultural legitimacy. This research employs a descriptive qualitative method through interviews with 17 informants and secondary data sources. The findings show that Ibu Nyai’s campaign is implicit in nature, utilizing socio-religious spaces and internal networks. Although it is non-confrontational and operates through cultural legitimacy, her influence is significant, as the solid and unified support of women voters is capable of shaping voter attitudes.